Diversity in the Maps of a Lisbon Neighbourhood: Community and ‘Official’ Discourses about the Renewed Mouraria - Bettencourt, Leonor; Castro, Paula (Culture and Local Governance / Culture et gouvernance locale, 2015)
The neighbourhood of Mouraria in the center of Lisbon is today home to three main groups of residents: traditional residents, new gentrifiers, and immigrants. This diversity is simultaneously a strength of and a threat to its social cohesion and its current urban rehabilitation process, undertaken by the City Council of Lisbon (CCL). This study has three main goals: 1) to analyze how the ‘community identity’ maps of the neighbourhood are constructed by residents’ discourse; 2) to analyze how the ‘official’ cultural map of the neighbourhood is constructed in the discourses of the press and the CCL; and 3) to compare the ‘official’ and the ‘community’ maps. In drafting the ‘community’ maps, 22 interviews were conducted with traditional residents (14), new gentrifiers (6), and immigrants (2). The ‘official’ cultural map was re-constructed through a press analysis (four articles from two reference newspapers: Público, 2014; Expresso, 2013) and an in-depth interview with the coordinator of the CCL office in Mouraria. Findings show that the rehabilitation program is represented in the ‘official’ discourse in a more positive way than in residents’ discourses. The main divergence concerns the targets of the intervention. However, in both discourses there is agreement regarding the social problems of Mouraria. The stories of the past told by traditional residents, although mentioning the loss of the traditional character of Mouraria, show the importance of public spaces for place attachment and place identity. The discourses of new residents highlight the role of places in building connections between past and present, and in helping maintain a sense of continuity. We discuss the importance of community identity mapping in understanding the ‘battle of ideas’ around urban rehabilitation and the impact that different perspectives can have. The study can be a source of information for decision-makers, helping strengthen the communication bridge between them and the community.